Towards measuring the economic value of higher education: lessons from South Africa. Issue 1 (2nd January 2017) - Allais, Stephanie
ABSTRACT: A crisis of student funding has led to most South African universities being closed for weeks, after protests in 2015 and again in 2016. A policy response to these events requires insight into relationships between higher education, society, and the economy. This paper interrogates the assumptions which underpin current approaches to measuring higher education in South Africa. It argues that analyses of labour market relationships, associated with forms of measurement linked to rates of return, graduate tracer studies, and employer requirements and satisfaction studies, give us a snapshot of relatively contemporary data, but do not tell much about the dynamics of causation. They contain interesting information but should not be used to overclaim about the relationship between higher education and the economy. Taken together with other approaches to higher education evaluation, they tell us more about how labour markets are looking for distinctions between candidates than about the value that higher education adds to societies and economies. A clear public policy response needs better forms of measurement and better tools of analysis.